2018
DOI: 10.1161/str.49.suppl_1.tp408
|View full text |Cite
|
Sign up to set email alerts
|

Abstract TP408: Uric Acid and the Risk of Recurrent Vascular Events and Mortality in Ischemic Stroke Patients: A 5-year Analysis

Abstract: Background: Women have generally lower levels of uric acid compared with men, yet their long-term prognostic impact is unclear in ischemic stroke patients. This study aims to investigate the significance of serum uric acid in relation to 5-year recurrent vascular events and mortality in ischemic stroke patients. Methods: Consecutive patients with acute ischemic stroke were recruited from the National University Hospital, Singapore, between January 2011 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Through the evaluation of the full text, 34 articles were excluded for the following reasons: review articles (n = 12); no mean or SD was reported (n = 6); significant dietary elements (n = 4); letter to the editor (n = 12). After the qualification assessment, 4 articles with a total of 2452 patients were included for the final analysis [17][18][19][20]. The standard traits of the research included in this meta-analysis are presented in ▶table 1.…”
Section: Literature Retrieval and Research Traitsmentioning
confidence: 99%
“…Through the evaluation of the full text, 34 articles were excluded for the following reasons: review articles (n = 12); no mean or SD was reported (n = 6); significant dietary elements (n = 4); letter to the editor (n = 12). After the qualification assessment, 4 articles with a total of 2452 patients were included for the final analysis [17][18][19][20]. The standard traits of the research included in this meta-analysis are presented in ▶table 1.…”
Section: Literature Retrieval and Research Traitsmentioning
confidence: 99%